The practice of biodiversity −related indigenous knowledge in Kota Belud, Sabah: a preliminary study - Adam, Anis Amalina; Othman, Normala; Ab. Halim, Adlina; Ismail, Sri Rahayu; Abu Samah, Asnarulkhadi (Universiti Putra Malaysia Press, 2019)
Indigenous knowledge is a set of principles, skills, practices, rituals, and customs developed by a particular race, inherited from generation to generation. Indigenous knowledge offers a unique and holistic understanding towards every aspect of life. In biodiversity conservation, integrating indigenous knowledge has become a trend. In many studies, indigenous knowledge has been proven to present a more human ecological approach to manage biodiversity loss. This paper aims to explore the practice of indigenous knowledge by looking at three components of indigenous knowledge system viz. agriculture, traditional medicine, and river management. A preliminary study was conducted in Kota Belud. Data was collected through a focus group discussion through purposively sampled informants consisting of Bajau, Dusun, and Iranun. The findings of the study revealed that the indigenous peoples in Kota Belud still practiced their knowledge. This study also emerges some issues related to indigenous knowledge mainly in knowledge degradation.